The effect of using digital mind mapping on cognitive achievement and performance level of some basic skills in handball - Khaled Thabet Awad; Ahmed Maget Hegazy (Turkish Journal of Kinesiology, 2016)
This study aims to identify the effect of using digital mind maps to on the cognitive achievement and the performance level of some basic skills in handball. Research population includes the first-year students at the Faculty of Physical Education in Port Said consisting of 200 students. Research Sample both researchers randomly selected the sample of first year students. The total sample size reaches 180 students with a 90.00%, after excluding failed students, re-registered students, the students of other levels of curriculum, practitioners to previous experiences and irregular students. The total number was 20 students with a percentage of (10.00%). They were divided into: Basic Sample: includes 80 students with a 44.44%. They were divided into two equal groups of 40 students. First Exploratory Sample: includes 60 students from the same research population and from outside the basic sample in order to find Tests Validity of the tests with a 33.33%. Second Exploratory Sample: includes 40 students from the same research population and from outside the basic sample in order to find Tests Reliability of the tests and identify the extent of pilot program appropriateness for the sample under discussion with a 22.22%. The first-year students were selected, according to the study plan, which contains a handball curriculum for the students of this educational level. Statistical Treatments: Both researchers conducted data statistically processes, using a statistical package for Social Sciences, SPSS ver. 20.0, in order to identify: arithmetic mean, standard deviation, median, skewness coefficient, correlation coefficient, discriminant validity coefficient, "t" test per one group, "t" test per two groups. The use of mind maps has a positive effect better than (explanation and model) method on the cognitive achievement and the performance level of some basic skills in handball. Active learning techniques, such as the method of digital mind maps in teaching handball curriculum for the students of Faculty of Physical Education should be used.